ANALISIS MODEL KEPUASAN KONSUMEN BERDASARKAN PENGARUH KEUNIKAN NAMA USAHA DAN NILAI KULINER - Setiawan, Andi (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2012)
This article is a research for researchers in marketing, particularly brand. This article is formulated based on the record and the facts that are found in the field. Facts where industria culinary competition at this time spawned creativity in finding a name that has a unique culinary efforts. uniqueness is on one side in an effort to build differentiation to competitors and at the same time aim to influence customer satisfaction. This article attempts to explore further the factors that lead to a better culinary value and how the value of culinary and business name to be determinants of consumer satisfaction. Formulation variables and indicators refer to previous research studies. A model has been developed and three hypotheses have been formulated to address the research problem. The sampling technique is quota sampling. Respondents of this research were 100 respondents, of which the respondent is a consumer culinary Semarang. Data analysis tool used is Structural Equation Modelling (SEM) in AMOS 16.0 program. The results of the data analysis of this study suggests a third model and research hypothesis can be accepted. Managerial Implications give advice to focus on the influence of culinary value to customer satisfaction culinary in Semarang. Key Word: Brand name, culinary value and customer satisfaction